Identity Based Secured Distributed Data Storage Schemes (International Journal of Engineering and Computer Science, 2015)
Identity based secured distributed data storage is such a scheme that reduces the load of an owner to maintain excessive number of files. Hence, it reduces the ramification of the owner to take care of all the files that he has with him. In this, the owner passes his files to the mediator between the owner and the user that is the proxy server. The proxy server plays an important role in this scheme. It encrypts the files that are given to him by the owner that are encrypted once, without having any cognition about the contents of the files. The proxy server also stores these encrypted files and gives the files to the authenticated users. When these files are given to the proxy server, the owner deletes those files from his system for the benefit of space efficiency. Hence, it is necessary to carefully examine the issues of confidentiality and integrity of the outsourced files. IBSDDS schemes possesses the properties: firstly, the file owner can decide access permission independently for each file and secondly, a user can access only one file for a single query. Resultantly, by using this scheme, the collusion attacks, means the disambiguation of data can be avoided.